Pengembangan Kapasitas Manajemen Sumber Daya Manusia Di Sektor Publik - Enni Iriani (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
Fast dramatic and unpredictable change of world has a wide consequences on the changing role of government, citizens, organisations and society. This requires both public and private organisations to reform themselves and their management system so as to get to their highest capacity. In terms of regional government, organizational capacity is the ability and competency of government as well as the efficiency in planning, implementing, managing and evaluating policies, strategies or programs designed for the impacts on the society. In the framework of the organizational capacity, human resource management devellopment is an important dimension for develoving the internal capacity of organization. The article begins with an explanation of the backgrounds that shows the importance for develoving the organizational capacity of public sector, then continues by presenting some HR experts experiences, their principles and methodsin meansuring and evaluating HRM capacity in their countries. It finally discuss some normative but applicative prescriptions for develoving the internal.